Marketing Efficiency of Corn Across Different Supply Chains in East Java - Heryanto, Andika Yuli (JASc (Journal of Agribusiness Sciences), 2025)
Corn production in East Java Province in the first quarter reached 42.50%, which caused the corn supply to be unstable. The disparity in prices between farmers and consumers results in losses for farmers. The large number of supply chain actors causes profits to decrease. The research focuses on supply chain analysis related to each pattern's product, financial, and information flow. Apart from that, it discusses marketing efficiency analysis. Primary data collection used direct observation and in-depth interviews. The sampling method uses convenience and snowball sampling. The research results show four supply chain patterns with supply chain actors: farmers, collector traders, large traders, and consumers. The payment methods used are direct and temporary payments. Important information needed by supply chain actors is corn prices, corn standardization, corn packaging, delivery schedules, and estimates of the amount of corn sent. Efficient marketing is in the second and fourth supply chain patterns because the profit margin ratio is more than one. The profit margin ratio values for farmers and collector traders in the second pattern are 1.52 and 1.94, which indicate that marketing is efficient. The value of the profit margin ratio for farmers in the fourth pattern is 1.46, so marketing is efficient.